A CHILD WITH TETRALOGY OF FALLOT PRESENTING WITH COMPLICATIONS OF INFECTIVE ENDOCARDITIS, CEREBRAL ABSCESS, AND UNDERNUTRITION - Yasmin, AA Ayu Dwi Adelia; Gunawijaya, Eka (Medicina, 2015)
Tetralogy of Fallot (TOF) is a congenital heart disease that consists of four anatomical anomalies,namely ventricular septal defect, pulmonary stenosis or obstruction of the right ventricular outflowtract, right ventricular hypertrophy, and overriding aorta. Tetralogy of Fallot is frequently associatedwith complications that could affect morbidity and mortality because of its complex cardiac lesions.Good understanding of the natural history and complications of this disease is very important to guidethe management of patients. We reported a 4-year old girl with classic TOF with complications ofinfective endocarditis, cerebral abscess, and undernutrition. Despite optimal medical therapy, thepatient?s condition showed no satisfying improvement. Since the parents were refused to take moreaggressive measure by undergoing surgical therapy, so that patient care remains focused on supportiveand palliative aspects. [MEDICINA 2015;46:37-41].Tetralogy of Fallot (TOF) merupakan suatu penyakit jantung kongenital yang terdiri dari empat anomalianatomis, antara lain ventricular septal defect, pulmonary stenosis atau obstruksi pada right ventricleoutflow tract, hipertrofi ventrikel kanan, dan overriding aorta. Tetralogy of Fallot sering disertai denganberbagai komplikasi yang dapat mempengaruhi morbiditas dan mortalitas karena kelainan inimerupakan kelainan kongenital kardiak yang kompleks. Pemahaman yang baik mengenai perjalananalamiah dan komplikasi penyakit ini sangat penting untuk mengetahui penatalaksanaan pasien.Kami melaporkan seorang anak perempuan berusia 4 tahun dengan TOF klasik yang juga menderitakomplikasi endocarditis infektif, abses serebral, dan gizi kurang. Walaupun telah memperoleh terapimedikamentosa yang optimal, kondisi pasien tidak menunjukkan perbaikan yang memuaskan.Orangtua pasien telah menolak pemberian tindakan yang lebih agresif, yaitu dengan terapipembedahan, oleh karena itu penatalaksanaan pasien lebih difokuskan pada aspek suportif danpaliatif. [MEDICINA 2015;46:37-41].